Emissions of intermediate-volatility and semi-volatile organic compounds from domestic fuels used in Delhi, India - Stewart, Gareth J.; Nelson, Beth S.; Acton, W. Joe F.; Vaughan, Adam R.; Farren, Naomi J.; Hopkins, James R.; Ward, Martyn W.; Swift, Stefan J.; Arya, Rahul; Mondal, Arnab; Jangirh, Ritu; Ahlawat, Sakshi; et al. (European Geosciences Union (EGU), 2021)
Biomass burning emits significant quantities of intermediate-volatility and semi-volatile organic compounds (I/SVOCs) in a complex mixture, probably containing many thousands of chemical species. These components are significantly more toxic and have poorly understood chemistry compared to volatile organic compounds routinely quantified in ambient air; however, analysis of I/SVOCs presents a difficult analytical challenge. The gases and particles emitted during the test combustion of a range of domestic solid fuels collected from across Delhi were sampled and analysed. Organic aerosol was collected onto Teflon (PTFE) filters, and residual low-volatility gases were adsorbed to the surface of solid-phase extraction (SPE) discs. A new method relying on accelerated solvent extraction (ASE) coupled to comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry (GC × GC–ToF-MS) was developed. This highly sensitive and powerful analytical technique enabled over 3000 peaks from I/SVOC species with unique mass spectra to be detected. A total of 15 %–100 % of gas-phase emissions and 7 %–100 % of particle-phase emissions were characterised. The method was analysed for suitability to make quantitative measurements of I/SVOCs using SPE discs. Analysis of SPE discs indicated phenolic and furanic compounds were important for gas-phase I/SVOC emissions and levoglucosan to the aerosol phase. Gas- and particle-phase emission factors for 21 polycyclic aromatic hydrocarbons (PAHs) were derived, including 16 compounds listed by the US EPA as priority pollutants. Gas-phase emissions were dominated by smaller PAHs. The new emission factors were measured (mg kg−1) for PAHs from combustion of cow dung cake (615), municipal solid waste (1022), crop residue (747), sawdust (1236), fuelwood (247), charcoal (151) and liquefied petroleum gas (56). The results of this study indicate that cow dung cake and municipal solid waste burning are likely to be significant PAH sources, and further study is required to quantify their impact alongside emissions from fuelwood burning.